Mobile Money Market Operations in the Financial Sector: Issues of Financial Inclusion, Savings Mobilization and Investment in Local Economy of Ghana (Global Journal of Management and Business Research, 2019)
The importance of the financial sector in an economy cannot be overemphasized. Among others, it provides financial resources to support businesses, household consumption as well as public sector investment. However, there is limited access to the facilities provided by the sector in Ghana, hence many people are excluded from benefits that could be obtained from the financial sector. In other words financial exclusiveness is a major challenge in the country. Therefore, introduction of Mobile telecommunication technology and its attendant Mobile Money Market have been received with appreciation to the service providers. Given the modus operandi of the new system it has become necessary to examine the innovation in relation to some variables which influence economic growth as it is expected of activities in the financial sector. Hence some research questions were raised to guide a study in the Mobile Money Market. Has the introduction of Mobile Money Market reduced financial exclusion? To what extent do households use the innovation to mobilize domestic savings? How are the funds in the Mobile Money Market utilized by the owners among others.
Keywords: telecommunication technology; service providers; money market; financial inclusion; savings